The man who lived underground : a novel - Wright, Richard, 1908-1960 (Library of America, 2021)
"Fred Daniels, a Black man, is picked up by the police after a brutal double murder and tortured until he confesses to a crime he did not commit. After signing a confession, he escapes from custody and flees into the city's sewer system."--